Occurrence of 80 per and polyfluorinated alkyl substances (PFAS) in muscle and liver tissues of marine mammals of the St. Lawrence Estuary and Gulf, Quebec, Canada - Khalid, Nejumal Kannankeril; Le Calvez, Maud; Lemire, Mélanie; Dinh, Quoc Tuc; Fontaine, Justine; Lair, Stéphane; Sauvé, Sébastien (Frontiers in Environmental Chemistry, 2024)
Limited data are available for the occurrence of more recent perfluoroalkyl substances (PFAS) in marine mammals, especially from the St. Lawrence Estuary and Gulf. This study investigates the occurrence of PFAS in liver and muscle tissues of various marine mammals, including the harbor seal, gray seal, harp seal, hooded seal, harbor porpoise, white-sided dolphin, white-beaked dolphin, and True's beaked whale. Among the 80 target PFAS (including PFCAs, PFSAs, Cyclic PFSA, FASAs/FASAAs, FTCAs/FTUCAs, FTSAs, Ether-PFAS, diPAPs and ESI+ ECF precursors) perfluorooctanoic sulfonate (PFOS) dominates in all the marine mammal species and several other long-chain PFCAs, such as PFNA, PFDA, PFUnA, PFTrDA, and PFHxDA, were detected at 100% frequency in both muscle and liver samples. PFDoA and 7:3 fluorotelomer carboxylic acid (7:3 acid) also showed a 100% detection frequency for liver samples. Harp seal tissues displayed notably low PFAS concentrations, with average total PFAS concentrations of 7 ng/g (ww: wet weight) in muscle and 44 ng/g (ww) in the liver. In contrast, the white-sided dolphin exhibited the highest average concentrations, reaching 39 ng/g (ww) in muscle and 334 ng/g (ww) in liver samples. The Pearson correlation analysis reveals a strong correlation between the concentration of PFOS, perfluoroalkyl carboxylic acids (PFCAs), and electrochemical fluorination (ECF) precursors. Species at the top of the marine food chain (harbor porpoise, white sided dolphin, and white beaked dolphin) presented the highest concentrations of PFAS, particularly PFOS and longchain PFCAs, highlighting the need for an increased regulation of these persistent molecules in order to protect marine mammal's health.